Enhanced charge storage of nanometric ζ-V2O5 in Mg electrolytes. Issue 43 (2nd November 2020) - Johnson, Ian D.; Nolis, Gene; Yin, Liang; Yoo, Hyun Deog; Parajuli, Prakash; Mukherjee, Arijita; Andrews, Justin L.; Lopez, Mario; Klie, Robert F.; Banerjee, Sarbajit; Ingram, Brian J.; Lapidus, Saul; et al.
Abstract : Nanometric ζ-V2 O5 displayes an enhanced ability to reversibly store Mg 2+, yielding a better understanding of kinetic limiting factors in reversible magnesiation reactions of oxide electrode materials. Abstract : V2 O5 is of interest as a Mg intercalation electrode material for Mg batteries, both in its thermodynamically stable layered polymorph (α-V2 O5 ) and in its metastable tunnel structure (ζ-V2 O5 ). However, such oxide cathodes typically display poor Mg insertion/removal kinetics, with large voltage hysteresis. Herein, we report the synthesis and evaluation of nanosized ( ca . 100 nm) ζ-V2 O5 in Mg-ion cells, which displays significantly enhanced electrochemical kinetics compared to microsized ζ-V2 O5 . This effect results in a significant boost in stable discharge capacity (130 mA h g −1 ) compared to bulk ζ-V2 O5 (70 mA h g −1 ), with reduced voltage hysteresis (1.0 V compared to 1.4 V). This study reveals significant advancements in the use of ζ-V2 O5 for Mg-based energy storage and yields a better understanding of the kinetic limiting factors for reversible magnesiation reactions into such phases.